2009
DOI: 10.1017/s1047951109990382
|View full text |Cite
|
Sign up to set email alerts
|

Functional state following the Fontan procedure

Abstract: Background Despite improvements in outcomes after completion of the Fontan circulation, long-term functional state varies. We sought to identify pre- and postoperative characteristics associated with overall function. Methods and Results We analyzed data from 476 survivors with the Fontan circulation enrolled in the Pediatric Heart Network Fontan Cross-sectional Study. Mean age at creation of the Fontan circulation was 3.4 plus or minus 2.1 years, with a range from 0.7 to 17.5 years, and time since completio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…32 This finding is similar to those previously reported. 13 A larger study from the PHN showed a weak association between exercise performance and ventricular morphology, with the left-ventricle subgroup having a higher percentage of predicted maximum Vo 2 .…”
Section: Discussionsupporting
confidence: 93%
“…32 This finding is similar to those previously reported. 13 A larger study from the PHN showed a weak association between exercise performance and ventricular morphology, with the left-ventricle subgroup having a higher percentage of predicted maximum Vo 2 .…”
Section: Discussionsupporting
confidence: 93%
“…6, 7, 28-33 Although heart transplantation is an option for select patients with failing Fontan physiology, survival is significantly lower among patients with a prior Fontan operation compared to patients with other forms of congenital heart disease or cardiomyopathy. 34, 35 Thus, even if there are substantial on-going issues in patients with a BV circulation after FAV, the potential for improved long-term prognosis and survival compared to patients with a univentricular circulation is the real question.…”
Section: Discussionmentioning
confidence: 99%
“…Although early surgical survival has improved for infants with HLHS, staged univentricular palliation to a Fontan circulation carries significant lifelong morbidity and mortality [1][2][3][4]. A subset of patients with HLHS share a common pathophysiologic etiology; namely, severe aortic stenosis in utero with left ventricular (LV) dilation and dysfunction.…”
Section: Severe Midgestation Aortic Stenosis With Evolving Hypoplastimentioning
confidence: 99%